Desire and human flourishing: perspectives from positive psychology, moral education and virtue ethics - Bosch, Magdalena (Positive Education, 2020)
To be what one desires to be. The notion of habit and its educational value -- The Role of Desire in Action -- Education of Desire for Flourishing -- The Joy of Doing Good and Character Education -- Desire and Freedom: Are We Responsible for Our Emotions? -- The ethical value of motivation as an operative desire -- Harmonising reason and emotions: Common paths from Plato to contemporary trends in psychology -- Desire and Beauty -- The Education of Desire: Moderation or Reinforcement? -- Desire and Sensitivity -- Desire and madness: Platonic dialogues on education -- Moral education as education of desire in Plato’s Symposium -- Educating desire in Aristotle -- The right desire? -- The Stoics on the Education of Desire -- The Desire in Origen and Gregory of Nyssa -- The salvation of desire: Saint Augustine’s perspective -- The Education of Desire according to Aquinas -- Attention and Education: Key Ideas from Charles S. Peirce -- Desire in Freud -- Psychological key to educating desire: Healthy Family Lifestyles -- The Education of Desire and the Use of ICT -- Desire and the emotion of shame -- The emotional openness of wonder and admiration to educating our moral desires -- Advertising and desire -- Pedagogical reflection on desire and perspectives for an education of identity -- Contemplation, learning, teaching through love -- A way out of the dialectics of love and desire as the clue to an adequate education of desire -- Rectification of Appetite’ as Education of Desire within ‘Moral’ Virtue.